2022-RA-620-ESGO Querleu-Morrow type A hysterectomy for low-risk early-stage (FIGO 2018 IA2-IB1) cervical cancer: a UK population-based retrospective cohort study. (20th October 2022) - Audrey Kwong, Fong Lien; Tranoulis, Anastasios; Yap, Jason; Elattar, Ahmed; Singh, Kavita; Balega, Janos
Abstract : Introduction/Background: To evaluate the long-term oncological outcomes in women with low-risk early-stage cervical cancer (CC) Methodology: Retrospective population-based study of prospectively collected data, spanning the period 2008–2020. Eligibility criteria were: (1) FIGO 2018 IA2-IB1, (2) squamous cell carcinoma or grade 1–2 adenocarcinoma, (3) absence of lympvovascular invasion (LVSI); (4) depth of invasion < 10 mm; (5) negative conization margins (including repeat cone); (6) negative imaging for nodal or distal metastatic disease. Associated factors, overall (OS) and progression-free (PFS) survival were analysed using the Kaplan-Meier method, Log-rank test and Cox regression. Post-operative complications were assessed via the Clavien-Dindo classification. Census day was April 1st, 2022. Statistical significance was set at p-value < 0.05. The statistical analysis was performed using Stata version 16.1. Results: 35 women fulfilled the criteria for enrolment. The median age at diagnosis was 43 years. FIGO stage was IA2 (75.8%) and IB1 (24.2%). Pelvic lymphadenectomy was performed in 53.4% of the cases. Lymphadenectomy omitted in 16 women with stage IA2 and LVSI-negative post-conization completely excised disease. Residual disease in the post-conization hysterectomy specimen was 1/35 (2.9%). Median follow-up was 83.00 (95% CI 24.00 – 159.00) months. During the follow-up period only one recurrence was observed, which resulted in a cumulative 2-year PFS of 97.1%. Mean PFS was 154.96 (95% CI 147.20 – 162.71) months. No severe (Clavien-Dindo >3) post-operative complications were noted. Conclusion: Our data demonstrated that Type A hysterectomy is safe and effective for selective women with early-stage low-risk CC. This evidence is in line with the recent prospective ConCerv trial. Further studies are warranted to draw firmer conclusions.